2005
DOI: 10.1002/env.723
|View full text |Cite
|
Sign up to set email alerts
|

Mapping sea bird densities over the North Sea: spatially aggregated estimates and temporal changes

Abstract: SUMMARYIn the Dutch sector of the North Sea, sea bird densities are recorded bi-monthly by using airborne striptransect monitoring. From these data we try to estimate: (i) high-resolution spatial patterns of sea bird densities; (ii) low-resolution spatial-average bird densities for large areas; and (iii) temporal changes in (i) and (ii), using data on Fulmaris glacialis as an example. For spatial estimation, we combined Poisson regression for modelling the trend as a function of water depth and distance to coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…In particular, this study assumes that the DF incidence over the study area can be modeled as a space-time Poisson process in which the mean of DF incidence cases is expressed as the product of a purely temporal term (driven primarily by climatic variation) and a space-time term (accounting for ratios between the recorded incidences and climate-driven incidences obtained by pure time-series modeling). Poisson regression models have been applied in spatial geostatistics studies (Diggle et al 1998;Pebesma et al 2005). In the present work, we use the Poisson model in a composite space-time domain.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, this study assumes that the DF incidence over the study area can be modeled as a space-time Poisson process in which the mean of DF incidence cases is expressed as the product of a purely temporal term (driven primarily by climatic variation) and a space-time term (accounting for ratios between the recorded incidences and climate-driven incidences obtained by pure time-series modeling). Poisson regression models have been applied in spatial geostatistics studies (Diggle et al 1998;Pebesma et al 2005). In the present work, we use the Poisson model in a composite space-time domain.…”
Section: Methodsmentioning
confidence: 99%
“…Hy-63 brid spatial/niche-analysis SDMs have been suggested 64 also by Allouche et al (2008). Pebesma et al (2005) 65 demonstrates that geostatistics is fit to be used with 66 spatio-temporal species occurrence records. Analysis of 67 spatial auto-correlation and its use in species distribu-68 tion models is now a major research issue in ecology and 69 biogeography ( Engler et al (2004) suggested a hybrid approach to 72 spatial modeling of occurrence-only records -a combi-73 nation of Generalized Linear Model (GLM) and ENFA.…”
mentioning
confidence: 99%
“…7) can be indeed reproduced 54 also from a representative sample (n=721). 55 We proceed with preparing the environmental predic-56 tors and testing their correlation with the density val-57 ues. We can extend the original single auxiliary map 58 (DEM) by adding some hydrological parameters: slope, 59 topographic wetness index and altitude above channel 60 network (all derived in SAGA GIS).…”
mentioning
confidence: 99%
“…This method results in a continuum of interpolated information conformed by predicted pixels. Due to its robustness, this method is widely used in several disciplines and is starting to become common in ecological studies [33,[52][53][54]. To generate interpolated information based on our butterfly surveys, we square root transformed the observed abundances per sampling site in order to comply with normality and skewness [55].…”
Section: Discussionmentioning
confidence: 99%